Time minimization in flexible robotic cells considering intermediate input buffers: a comparative study of three well-known problems - Nejad, Mazyar Ghadiri; Guden, Huseyin; Vizvari, Bela (Taylor & Francis Ltd, 2019)
Flexible manufacturing cells are widely used in many real-life industries. These cells contain a group of highly automated machines, the input station, and the output station that are interconnected by a robot which handles the materials, automatically. The system repeats a cycle in its long run, and the cycle time depends on the order of the loading/unloading activities which are performed by the robot. To achieve the most efficient use of these cells, order of the robot activities must be determined. This study is motivated by such a real life system with intermediate machine buffers. First, a mathematical model is presented. Then, to decrease the solution time, a modification of the model is proposed. Additionally, another model is proposed to find the maximum processing time of the machines when the cycle time is known. An assignment problem method is utilized to optimize the cyclic production, and performances of all the proposed methods are examined using several numerical instances. Finally, the performance of the considered system is compared with no intermediate machine buffers system, and also it is compared with the system utilizing a dual-gripper robot. The results show that performances of the three robotic cells are non-identical in practice.
Keywords: Flexible manufacturing system; Robotic cell; Cyclic scheduling; Integer programming; with-intermediate input buffer; Dual-gripper robot